ATPasas tipo P de Mycobacterium tuberculosis como dianas para el diseño racional de compuestos antituberculosos (2020)
Tuberculosis (TB) is an infectious disease caused by the acid-fast bacillus Mycobacterium tuberculosis (Mtb), which is one of the most important public health problems worldwide. Furthermore, the emergence of resistant Mtb strains to current anti-TB drugs has increased the search for alternative therapeutic targets and methods for the rational design of new effective drugs. In this sense, membrane proteins have been considered interesting targets due to their biological implication and for being highly accessible to active compounds. Particularly, P-type ATPases membrane transporters are interesting targets due to their implication in ionic homeostasis and mycobacterial viability. This work was oriented to CtpF, a calcium P-type ATPase, related to a broad number of biological conditions associated to processes of infection such as oxidative stress, adaptation of tubercle bacilli to anaerobic conditions, hypoxia and latency. Due to that, the main objective of this doctoral Thesis was to determine, through in silico and in vitro analysis, the potential of P-type ATPases of Mtb, especially the calcium transporter CtpF, as a target for the rational design of anti-TB compounds. Initially, a 3D homology model of CtpF was generated, which was employed for identified key pharmacophoric features of the CtpF-cyclopiazonic acid (CPA) complex, a well-known inhibitor of the sarco-endoplasmic reticulum Ca2+-ATPase (SERCA1a), from which its 3D structure is known experimentally and was used as a template in the construction of the model. By using a repertoire of experimental techniques, it was evaluated and found that CPA causes inhibition of the Ca2+-ATPase activity of CtpF, as well as mycobactericidal activity. The analysis of the transcriptional response of P2 ATPases to treatment with CPA showed a specific response of ctpF in comparison with other P-type ATPases. These initial results provide evidence that CtpF is a molecular target for the design of compounds with anti-TB potential. Thereupon, with the CtpF-CPA pharmacophoric features, a pharmacophore-based virtual screening was performed using the ZINC database in order to select candidate molecules to inhibitors of CtpF. Molecular docking-based virtual screening and binding free energy calculations (MM-GBSA) of selected candidates allowed identifying six compounds with the best relative binding energies to be evaluated in vitro. The compounds selected displayed in vitro antimycobacterial activity, showing a minimum inhibitory concentrations (MIC) ranging from 50 -100 μg/mL, and growth inhibitions of 29.5 - 64.0 % on Mtb. Likewise, they causes inhibition of Ca2+-ATPase activity in Mtb membrane vesicles (IC50) ranging from 4.1 - 35.8 μM. Finally, the activity of the compounds with the best biological activity was evaluated in a macrophage infection model, as an approach to evaluate the effect of compounds once the infection has occurred. The compound ZINC63908257 was the best candidate by displaying a MIC of 50 μg/mL, a Ca2+ P-type ATPase inhibition with IC50 = 4.4 μM and 81 % decrease in Mtb replication within macrophage. This compound showed cytotoxic activity of 12.9 % in MH-S cells and hemolysis of 2 % of human erythrocytes, thus, this compound shows a good pharmacokinetic profile (drug-like). Overall, the results presented here shows the importance of the P-type ATPases of Mtb for the mycobacteria survival during infection, and identify the CtpF as a key molecular target for the design of new antituberculous compounds.